The Effect of Acupressure Therapy on Reducing Blood Pressure in Hypertension Patients in the Work Area of the Muntok Health Center in 2022 - Kiki Amalia (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study was to determine the effect of giving acupressure therapy on reducing blood pressure in hypertensive patients in the Working Area of the Muntok Health Center in 2022. This research method used a Pre-Experimental with a One Group Pretest-Posttest design. The sample used in this study were 14 people. The results of this study revealed that there was an effect of acupressure therapy on reducing blood pressure using non-parametric statistical methods and using the Wilcoxon test obtained a value of p = 0.001 (p <0.05) in systolic and diastolic blood pressure, before and after acupressure therapy with an average systolic pretest blood pressure 150.71 and 127.14, while posttest diastolic 90.36 and 80.71. The conclusion of this study is that acupressure therapy is an alternative therapy that can treat patients with hypertension.